Is Teaching a Deaf Student in an Inclusive English Classroom Challenging? A Qualitative Case Study - Lisya Anggi Sapitry; Saharudin Saharudin; Mukhlas Abrar; Hadiyanto Hadiyanto (Journal of Educational Sciences, 2026)
Inclusive English classrooms require teachers to provide meaningful access for students whose learning needs differ from those of the majority. This qualitative case study examined how an English teacher perceived the difficulty of teaching a deaf student and identified the challenges that appeared in classroom practice. Data were obtained from a semi-structured teacher interview and classroom observation at an Integrated Islamic School in Jambi, Indonesia, and were analyzed thematically. The findings indicate that teaching the student was perceived as moderately challenging rather than extremely difficult. The student participated successfully in written and visually supported tasks, but experienced barriers when lessons depended on oral instructions, listening, pronunciation, and spontaneous interaction. Four themes were identified: moderate teaching difficulty requiring pedagogical adjustment; communication and instructional accessibility; support, participation, and classroom relationships; and institutional readiness and the inclusive-classroom dilemma. Visual media, written explanations, gestures, repetition, and assistant-teacher mediation supported access, although academic participation remained limited. The study concludes that difficulty arises primarily from the accessibility of instruction rather than from the student's inability to learn. More specific teacher training, collaborative planning, and differentiated multimodal instruction are therefore needed.